1992
DOI: 10.2136/sssaj1992.03615995005600060035x
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of a Soil‐Landscape Model for Predicting Soil Drainage Class

Abstract: The soil‐landscape relationships frequently used for soil mapping activities are seldom documented. We developed a statistical model that relates soil drainage classes to eight landscape parameters describing slope morphology, proximity to surface drainage features, and soil parent material. Soil profiles and landscape parameters were described at 305 randomly selected sampling points within the Mifflintown 7.5‐min topographic quadrangle in the unglaciated ridge and valley physiographic province of central Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…Much of the early development of the soil factor equation can be attributed to Jenny and Leonard (1934) and Jenny (1941) who sought to validate the soil factor equation by relating changes in soil properties to changes in climate across a WestEast transect in the United States. Since then there has been a large body of literature that relates soil properties to landscape characteristics (e.g., Walker et al, 1968;Kreznor et al, 1989;Bell et al, 1992;Odeh et al, 1994). Computer technology has made environmental variables more readily available and facilitated a greater pursuit of quantitative relationships with soil properties.…”
Section: Model Strategymentioning
confidence: 99%
“…Much of the early development of the soil factor equation can be attributed to Jenny and Leonard (1934) and Jenny (1941) who sought to validate the soil factor equation by relating changes in soil properties to changes in climate across a WestEast transect in the United States. Since then there has been a large body of literature that relates soil properties to landscape characteristics (e.g., Walker et al, 1968;Kreznor et al, 1989;Bell et al, 1992;Odeh et al, 1994). Computer technology has made environmental variables more readily available and facilitated a greater pursuit of quantitative relationships with soil properties.…”
Section: Model Strategymentioning
confidence: 99%
“…Soil organic C (SOC) storage and dynamics have frequently been the focus of soil-landscape modeling efforts (Arrouays et al, 1995(Arrouays et al, , 1998Bell et al, 2000;Chaplot et al, 2001;Abnee et al, 2004a,b;Terra et al, 2004;Thompson and Kolka, 2005). Hydric and hydromorphic soil delineation (Thompson et al, 1997;Chaplot et al, 2000), net primary productivity (Gessler et al, 2000), soil drainage class (Bell et al, 1992, and soil water dynamics (Chamran et al, 2002) have also been successfully modeled.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (Bell et al, 1992Thompson et al, 1997;Chaplot et al, 2000;Thompson and Kolka, 2005) have employed an independent data set (collected from the same study site and not used in model development) to validate their models. Chaplot et al (2003) have provided the most rigorous test of model transportability across a region.…”
Section: Introductionmentioning
confidence: 99%
“…Soil toposequences were developed to describe the way water moves through and over landscapes (Moore et al 1993;Thompson et al 1997Thompson et al , 1998Campling et al 2002). Bell et al (1992) developed a soil-landscape model to incorporate a variety of topographical and parent material data to predict soil drainage distributions in south-central Pennsylvania. The results showed that soil parent material was an important factor that explained 74% of the field observations when soil was classified into three drainage classes.…”
mentioning
confidence: 99%